Über Determinatoren im Deutschen und Polnischen - Koniuszaniec, Gabriela (Studia Germanica Posnaniensia, 2018)
The article discusses and compares the repertory and usage of determiners in German and Polish. Apart from the German article and its equivalents in Polish the author also discusses the other classes of determiners in both languages, such as demonstrative, possessive and indefinite pronouns, among them the so called quantificators. The similarities and differences are illustrated with examples of correct structures and structures with errors, i .e. by means of falsification.